1999
DOI: 10.1200/jco.1999.17.10.3064
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Factors for Patients With Metastatic Breast Cancer Undergoing Aggressive Induction Therapy Followed by High-Dose Chemotherapy With Autologous Stem-Cell Support

Abstract: The chance for long-term remission with induction therapy with AFM and high-dose chemotherapy is increased for hormone receptor positive-patients with nonvisceral metastases who have not received prior adjuvant chemotherapy and have long disease-free intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 11 publications
2
23
0
1
Order By: Relevance
“…The significance of HMGI-C mRNA detection in peripheral blood, even allowing for the relatively small number of patients with metastatic breast cancer studied here, implies that this is a particularly strong prognostic factor. The multivariate analysis also showed that the presence of lung and liver metastases was significantly associated with worse outcome, which is consistent with previous studies, as is the fact that patients who were oestrogen receptor positive had significantly better overall survival (Rizzieri et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The significance of HMGI-C mRNA detection in peripheral blood, even allowing for the relatively small number of patients with metastatic breast cancer studied here, implies that this is a particularly strong prognostic factor. The multivariate analysis also showed that the presence of lung and liver metastases was significantly associated with worse outcome, which is consistent with previous studies, as is the fact that patients who were oestrogen receptor positive had significantly better overall survival (Rizzieri et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…One area of intense breast cancer research has been in assessing prognostic factors of patient outcomes, and several molecular markers have been evaluated in association with established histologic and clinical prognostic parameters of breast cancer (Honkoop et al, 1998;Rizzieri et al, 1999;Sabbatini et al, 2000;Silva et al, 2001).…”
mentioning
confidence: 99%
“…Other trials of a single cycle of HDC have reported much higher conversion rates, ranging between 20 and 60%. [30][31][32] The low conversion rate observed following the first cycle of HDC in our trial may be explained in part by the chemotherapy agents used (CEP) and the relatively short interval (3 weeks) between treatment and the response assessment. 33 The value of HDC in the setting of metastatic breast cancer remains controversial and may in fact be limited, as noted in the ABMTR analysis, to specific patient subsets.…”
Section: Discussionmentioning
confidence: 95%
“…It is of note that extent of disease (number of metastatic site and visceral involvement) did not differ between HDC candidates and non-candidates, and was not included in the prognostic analyses. Adverse prognostic factors for patients entering HDC trials include previous adjuvant chemotherapy, liver metastases, extensive metastatic disease and chemoresistant disease (Ayash et al, 1995;Rizzieri et al, 1999;Rowlings et al, 1999).…”
Section: Discussionmentioning
confidence: 99%